Attending to 'culture' in intercultural language learning: a study of Indonesian language teachers in Australia. Issue 4 (3rd July 2020) - Naidu, Kate
ABSTRACT: In recent decades, the field of language teaching has been increasingly recognised as having an important role in developing not only linguistic proficiency, but also a kind of 'interculturality' among students. Despite this 'intercultural turn' being evident in academic and policy documents, language teachers are at varying stages in their adaptation to such an approach. This paper draws on empirical data from a small-scale study conducted with teachers of Indonesian in Australian schools, to elucidate teachers' understandings of their role as 'intercultural' educators. In particular, the notion of 'culture' is examined, and the ways it is deployed around ideas of 'intercultural understanding' and language teaching pedagogy. This paper argues that despite the prevalence of 'interculturality' in educational policy, and a prevailing 'intercultural ethos' amongst teachers, confusion persists around the foundational idea of 'culture', which may affect teaching philosophy and practice.